A SIMPLE CALCULATION OF GRAVITATIONAL LENSING ON THE ROTATING STARS - Norma Sidik Risdianto; Agung Laksana; Asih Melati (UIN Sunan Kalijaga Yogyakarta, 2018)
We propose a simple calculation to obtain the gravitational lensing on rotating stars. The calculation has been made by using a Lagrangian of Kerr metric and getting for deflection angle. The calculation has been reduced to slow-rotating stars and equatorials case () for maximum deflection angle.